Diagnostic evaluation application as requirement on course beginning for first baccalaureate "A" sciences on educational unit "El Carmen". (2020) - Zambrano, Alex Paúl; Zambrano, Ana Thalía Lucas; Zambrano, María De Los Ángeles Lucas
No abstract available